Learning of complex neurons - Kotsovsky, V. (Видавництво Львівської політехніки, 2015)
The paper deals with the problems of realization of Boolean functions on neural-like units with complex weight coefficients. The relation between classes of realizable function is considered for half-plane-like activation function. We also introduce the concept of sets separability, corresponding to our notion of neuron. The iterative online learning algorithm is proposed and sufficient conditions of its convergence are given.
Keywords: complex neuron; neural network; threshold unit; threshold function; learning